Teaching Peace in a Time of War - Ruether, Rosemary Radford (Dialog, 2003)
It is difficult to distinguish a time of war from a time of peace in America, because the Bush administration prosecutes its war on terrorism with an ongoing supporting economy. “Teaching Peace” means analyzing realistically the vested interests in perpetuating a state of war.